Lake Chad: Fluctuating Water Level and Its Implications for People’s Livelihood in the Area (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
This study assessed the fluctuating water level of Lake Chad and its consequences on the livelihood of people that depend on it. In terms of depth, Lake Chad is very shallow which makes it vulnerable to climate change and human activities. The study opined that continuous reduction in the volume of water of the lake will lead to negative effects such as forceful migration, resource-induced conflict, loss of biodiversity etc. Insurgency spear-headed by Nigeria based terrorist organization, “Boko Haram”, has killed many people including farmers and fishermen in the riparian countries of Nigeria, Niger, Chad and Cameroun and this has led to a decline in agricultural activities around the Lake Chad area making many to depend on food aid for their survival. The insurrectional activity of the terrorist group around the Lake Chad area also makes trade between communities extremely difficult as they are known to have attacked and killed people inside market. It is recommended that measures such as livelihood diversification through technology, creation of protected area, improved agricultural practices etc. should be adopted to reduce pressure on the lake and its resources.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(2), 2020, P 1-8